Penerapan Model Problem Based Learning Berbatuan Wordwall Untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Pada Mata Pelajaran Sejarah - Hasanah, Hudaidah, Wardiyah (LP4MK STKIP PGRI Lubuklinggau, 2025)
This article discusses the application of the problem based learning model assisted by wordwall media to improve students' critical thinking skills in history subjects at SMAN 2 Palembang. The research method used was classroom action research carried out in 2 cycles. Data collection uses observation sheet instruments, written tests and student worksheets. The results of the research showed that there was an increase in students' critical thinking skills, which in cycle 1 was 39.53% and in cycle 2 it was 83.72%.